Origin of the temporal stability control of living system nonequilibrium. (April 2023) - Cottam, Ron; Vounckx, Roger
Abstract: Following Ervin Bauer we accept that a living system can be characterized by its stable nonequilibrium. We represent such a system by a model hierarchy and relate system stability to computational delays across the hierarchy. For natural computation across the system assembly we advocate chaotic computation, and evaluate computational delay at the different organizational levels of the hierarchy. We compute inter-elemental access speed for the atomic and cell levels, and conclude that cell-related speed is 1000–10, 000 times that of the atom level, confirming that on moving from the system- as -itself level towards the system- as -atoms level overall level access speed reduces. We conclude that Bauer's living system description as a stable nonequilibrium is justified.